Aceh Cultural Elements in the Settlement Context - Wulanda, Destri; Santoso, Happy Ratna; Septanti, Dewi (IPTEK Journal of Proceedings Series, 2020)
Indonesia consists of various diverse tribes and cultures. Culture is the result of people's thoughts and behavior. Culture can also act as the identity of a tribe that has its characteristics. The difference in characteristics is interesting to study, one of which is the culture of Aceh in Indonesia. Aceh is rich in cultural values and customs because of its historical background. Influences from various backgrounds eventually shaped the characteristics of Acehnese. The culture of Aceh has been discussed in several studies, but no one has focused on the context of settlement. Therefore, this study was conducted to analyze aspects of Aceh's culture in a settlement. Cultural aspects can be analyzed based on world views, values, manifestations, activity systems, and social expressions. This study is a literature review, which uses secondary data to answer the research objectives. Secondary data were obtained from literature related to research topics, such as books, journals, regulations, etc. Furthermore, the data collected will be analyzed and concluded using descriptive analysis. The study results explain that every aspect of Aceh's culture refers to Islamic rules, where the balance between customary law and religious law is important for Acehnese lives.